Unveiling the Bacterial Diversity of Non-venomous Snakes: Insights from 16S rRNA Gene Sequencing and Phylogenetics - Sarsavan, Anil; Pawar, Manohar; Shehla Ishaque (International Journal of Scientific Research in Biological Sciences, 2024)
India experiences a high burden of snakebite fatalities, with secondary wound infections posing a significant additional threat. This study investigated the diversity of oral bacteria, including both pathogenic and non-pathogenic species, in the common non-venomous Indian rat snake (Ptyas mucosa) from Central India. Oral swabs were collected for bacterial isolation, followed by DNA extraction and bacterial identification via 16S rRNA gene amplification. All isolates were identified to the strain level, with their consensus sequences deposited in the NCBI Gen Bank database. Phylogenetic trees were generated using MEGA X software. We identified eight bacterial strains: Enterococcus faecalis strain yjd-wu, Lysinibacillus capsici strain PB300, Lysinibacillus fusiformis strain 24, Lysinibacillus macroides strain R154, Mammaliicoccus sciuri strain A-SD13, Mammaliicoccus sciuri strain FDAARGOS_285, Mesobacillus subterraneus strain HBPPPL1, and Mesobacillus subterraneus strain KI1. Among these, two strains were highly pathogenic to humans, and two were moderately pathogenic. Findings of the study show the presence of harmful bacteria in the oral cavity of non-venomous snakes, implying a risk of subsequent infections and wound problems after snakebite.